The Role of Green price in Formation Consumers Attitudes towards Green Products (Field Study on Consumers of Pharmaceutical in Syrian Cost) (Journal of Hama University, 2024)
Green pricing is an important dimension of green marketing, as corporate strategies today do not aim to achieve profit only, but rather to achieve sustainability among competitors. Therefore, green marketing has become one of the goals that companies seek to achieve, and companies must work to raise awareness among consumers about environmental issues. And make them feel that going green will make a difference.The research aimed to identify the impact of green pricing in Formation Consumers Attitudes towards Green Products in Syrian Cost.The researcher adopted the statistical method, and the preliminary data were collected through a questionnaire form as a tool for study, which was organized based on the researcher's knowledge of published literature, questionnaire was distributed to a sample of research that represented by 395 consumers. In order to test hypotheses, the researcher unloaded a database using SPSS issue 23 and adopted on Cronbach’s Alpha to measure the stability of the meter. The main result of the research was no existence of a fundamental role for the green pricing in Formation Consumers Attitudes towards Green Products in Lattakia, However, it is negative towards not agreeing to green pricing.
Keywords: Green marketing; Green price; Consumer Attitudes